2011
DOI: 10.1093/rheumatology/ker296
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab: a novel therapy for patients with large-vessel vasculitis

Abstract: In this small group of patients with LVV, treatment with TCZ was effective and well tolerated. Further, larger studies are required to confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
89
0
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(107 citation statements)
references
References 13 publications
7
89
0
11
Order By: Relevance
“…[20][21][22] We observed a "reverse remodeling" effect of TCZ on the thickened arterial walls in 2 patients in our study through continuous long-term administration of TCZ (Table II, Figure 1 and Figure 2), while we observed no worsening of the thickened arterial lesions in the other 2 patients. Furthermore, GC was tapered off in two patients (cases 3 and 4) and the dosage of GC was gradually decreased to 2 mg/day (case 1) and 3 mg/day (case 2) during this study period (Table II).…”
Section: Discussionsupporting
confidence: 46%
See 3 more Smart Citations
“…[20][21][22] We observed a "reverse remodeling" effect of TCZ on the thickened arterial walls in 2 patients in our study through continuous long-term administration of TCZ (Table II, Figure 1 and Figure 2), while we observed no worsening of the thickened arterial lesions in the other 2 patients. Furthermore, GC was tapered off in two patients (cases 3 and 4) and the dosage of GC was gradually decreased to 2 mg/day (case 1) and 3 mg/day (case 2) during this study period (Table II).…”
Section: Discussionsupporting
confidence: 46%
“…In 2011, Salvarani, et al reported a pilot study of 4 patients with LVV (2 with GCA and 2 with TA) treated with TCZ (8 mg/kg/month) for 6 months followed by MTX maintenance therapy. 20) Two patients were treatment-naïve and the other two patients had relapsing disease. Three patients entered complete clinical remission and 1 case achieved partial response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Számos kisebb tanulmány és esetriport is hatékonynak találta GCA kezelésében [39][40][41][42][43][44][45][46][47][48].…”
Section: öSszefoglaló Közleményunclassified